UJI LAMA PERENDAMAN DAN DOSIS PUPUK ORGANIK CAIR BIOLEMI TERHADAP PERTUMBUHAN VARIETAS INPARI 32 (Oryza sativa L.) DI PERSEMAIAN - Dyagung Prastio Yudistira; Widya Lestari; Badrul Ainy Dalimunthe (Jurnal Agroteknologi, 2022)
Until now, Indonesia's rice production has not been able to meet all the needs of the community. In the evaluation of seeds there are often seeds that are still abnormal and have not germinated. From the description above, the researcher is interested in examining "Test of immersion time and biolemi POC dosage on the growth of rice seeds of Inpari 32 (Oryza sativa L.) variety". This research was conducted in Perbaungan Village, Bilah Hulu District, South Labuhanbatu Regency, North Sumatra Province. This research used inpari 32 rice varieties with factorial randomized block design (RAK) method, with two factors, namely soaking time and biolemy POC. Soaking time affects the growth of rice seedlings on the parameters of seedling height, germination and root length. The application of biolemy liquid organic fertilizer had no significant effect on all parameters. The interaction of immersion time with the application of biolemy liquid organic fertilizer gave no significant effect on all observation parameters.